Accurate discrete modelling of stiffened isotropic and orthotropic rectangular plates. (December 2015) - Pydah, Anup; Bhaskar, K.
Abstract: An analytical approach is presented here for simply supported blade-stiffened rectangular plates wherein important non-classical effects such as transverse shear deformation and rotary inertia are carefully accounted for. The analysis differs from full three-dimensional modelling of both the plate and the stiffener in that a plane stress idealization is used to model the kinematics of transverse bending of the stiffener while simple one-dimensional classical models are employed for lateral bending and torsion. Parametric studies are used to highlight the importance of non-classical effects in plate and stiffener kinematics and to finally lead to certain recommendations for accurate modelling of stiffened plates. Abstract : Highlights: An accurate analytical formulation for blade-stiffened plates is presented. The three dimensional equations of elasticity are used to model the plate. A plane-stress formulation is used for transverse bending of stiffener. Transverse shear deformation in stiffened vs. nstiffened plates is highlighted. Recommendations given for accurate modelling of stiffened plates